Z-Plasty technique in congenital midline cervical cleft; a rare case report & literature review - Adi, Ghaith; Eckoldt, Felicitas; Alhussami, Ilmi (Frontiers in Surgery, 2025)
Congenital midline cervical cleft (CMCC) is a rare developmental anomaly of the anterior neck, often misdiagnosed due to its similarity to other cervical malformations. It results from impaired midline fusion of the branchial arches, leading to a linear skin defect with a fibrotic cord and, in some cases, a sinus tract. Left untreated, CMCC can cause progressive contracture, restricted neck mobility, and aesthetic deformities. This review examines the embryological basis, clinical presentation, histopathological characteristics, differential diagnosis, and surgical management of CMCC, with a focus on Z-plasty as the preferred reconstructive technique. Z-plasty effectively lengthens the scar, prevents recurrent contracture, and restores normal neck contour. In addition, we present a case of a 3-day-old female neonate with CMCC, successfully treated with Z-plasty reconstruction, reinforcing the importance of early intervention. Emerging genetic research suggests a potential hereditary component in CMCC, warranting further investigation into its molecular underpinnings. Advances in regenerative medicine and surgical innovation may improve treatment outcomes, offering new possibilities for personalized management of congenital cervical anomalies.